Aftermath of the war: Trauma and divided communities - Ajduković, Dean (Array, 2005)
Studies of long-term effects of the wars in the Balkans show that some of these communities remain fragmented and divided along different lines. Overwhelming feelings of trust and betrayal by the close neighbors and life-long friends remain high even years after the traumatizing experiences that devastated the communities. Interpersonal processes including loss of trust, disruption of social norms and decreasing quality in close social transactions at times leading to the war still characterize the reactions of community members. These experiences, together with massive trauma and losses inform the social context that prevents the healing of individuals and prolongs fragmentation of communities. Data from a series of studies will be used to analyze the long-term community reactions and discuss the interventions that can facilitate social reconstruction and trauma healing in such communities. These need to help decrease social tensions among groups that have been involved in a conflict, provide treatment for the most traumatized individuals and at the same time work towards re-connecting community members. In such a context, individual recovery from violence and community social reconstruction as two parallel, interdependent and non-linear processes.